Evaluation of Accompaniment Playing Course with the Perspective of Pre-Service Music Teachers - (:unkn) unknown (HACETTEPE UNIV, 2014)
In this study it was aimed to evaluate Accompaniment Playing course according to perspective of pre-service music teachers. The study group is composed of 56 students who receive education in third and fourth classes at Marmara University Ataturk Faculty of Education Department of Fine Arts Education. In the study, case study which is among the qualitative research patterns and scanning method which is among the quantitative research methods were used. In the study, easily accessible condition sampling was used which is one of the qualitative research methods, data obtained from a survey which is composed of seven open-ended questions were analyzed with descriptive analysis method. At the same time, the sufficiency levels of pre-service music teachers in Accompaniment Playing course were determined by observation form. As a result of the study, it was determined that the course hours and the fact that course is given in only single term is considered to be insufficient by pre-service music teachers, every student cannot play with accompaniment adequately during course, theoretical and practical studies carried out during course are functional about teaching profession, repertory studied in the course is suitable for elementary and secondary school music course, new and modern course instrument methods should be developed, pre-service music teachers think themselves capable of making decipher about accompaniment, accompaniment playing, writing accompaniment, adapting solo instrument or sound, listening to solo party. The results obtained depending on observation shows that the sufficiency of pre-service music teachers in Accompaniment Playing course is at medium level.
Keywords: Accompaniment Playing Course; pre-service music teachers; music teaching